CADANGAN SUMBERDAYA AIR UNTUK MENUNJANG PENGEMBANGAN WILAYAH KABUPATEN TASIKMALAYA - Hartanto, Priyo; Suriadarma, Ade; -, Saifudin (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Tasikmalaya District occupied the area of 2.680,47 km2 and located on the elevation between 0 to 3,000 m above sea level with hilly, highland, and slopy morphology. Dry month occurred on August, while wet months occurred on the period of September to July. The average monthly precipitation is ranged between 92 – 320 mm with total of yearly precipitation 2,532 mm. The monthly precipitation is ranged between 96 – 116 mm, with total of yearly evapotranspiration about 1,307 mm. Water reserves in Tasikmalaya District is ranged between 23 to 207 mm, covering in the area of 2,680.5 km2, then total of reserved water is 1,306,515 m3 to 11,758,655 m3. Water for domestic needs is 222.150 m3/day. 169.805 m3/day excess water can be used for approximately 117.920 hectares agriculture or approximately 393.067 hectares of land crops.